2016
DOI: 10.1080/09540121.2016.1164292
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy initiation and adherence in rural South Africa: community health workers’ perspectives on barriers and facilitators

Abstract: South Africa has the largest global HIV/AIDS epidemic, but barriers along the HIV care continuum prevent patients from initiating and adhering to antiretroviral therapy (ART). To qualitatively explore reasons for poor ART initiation and adherence rates from the unique perspective of community health workers (CHWs), we conducted focus groups during May–August 2014 with 21 CHWs in rural Msinga, KwaZulu-Natal. Interviews were audio-recorded, transcribed, and translated from Zulu into English. Hybrid deductive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 47 publications
(78 reference statements)
0
58
0
Order By: Relevance
“…medical, and financial assistance) to informational and emotional support. 21,43 CHWs serve a key role in HIV-related care by providing a consistent source of home-based HIV/ART education, counseling, and support for patients and family members. By building relationships with patients over time, CHWs can effectively mitigate barriers to care such as stigma, denial, inadequate patient education, and poor social support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…medical, and financial assistance) to informational and emotional support. 21,43 CHWs serve a key role in HIV-related care by providing a consistent source of home-based HIV/ART education, counseling, and support for patients and family members. By building relationships with patients over time, CHWs can effectively mitigate barriers to care such as stigma, denial, inadequate patient education, and poor social support.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one CHWs with ‡2 years of experience working in Msinga were recruited by phone for participation in one of three focus groups. 21 To provide a sample with broad geographic representation of the Msinga neighborhoods, these participants were purposively selected from a list of all 51 CHWs working for the aforementioned local NGO's homebased care branch. 21 Since it was founded in 1999, this NGO has been employing CHWs for community outreach, with a particular focus on HIV/AIDS.…”
Section: Participant Recruitment and Informed Consentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, numerous studies have examined the implications of traditional medicines and practices related to HIV treatment and management [2831]. The traditional healing system has been claimed to be illogical, lacking in both scientific validity and suitable policies for its products and practices [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Northern Namibian, 11% of respondents reported taking other traditional treatments together with ART [9]. It is noteworthy that a South African study reports that there is often tension between ARV treatment and alternative therapies [23]. Such beliefs present healthcare workers with a challenge to promote and foster adherence to ART among patients.…”
Section: Cultural and Religious Beliefs Related Factorsmentioning
confidence: 99%